Assessment of managerial innovation in manufacturing company - R Y H Silitonga; M Setiawati (Institut Teknologi Sepuluh Nopember, 2018)
Every company has to develop their managerial capability to maximize performance of every function in order to survive in an environment with drastic changes right now. This research was conducted at two governments owned manufacturing companies to compare the differences in managerial innovation. The method to assess the managerial innovation was based on elements of management function, which are planning, organizing, leading, controlling and coordinating. There were two methods in collecting the data, using questionnaire and doing observation. Questionnaires results were calculated using BPMSG AHP online system, to determine the score. The higher score of managerial innovation, the higher potential of the company to innovate. Managerial innovation score were 42.3% and 48.9%, which showed that none of them were innovative based on the previous research standard, which stated that innovation potential should be more than 50%. The differences between the two were also analysed based on every management function.